Hubungan Status Gizi dan Kebiasaan Berolahraga Terhadp Tingkat Kebugaran Jasmani Siswa Sekolah Dasar 2 Angkasa Kota Padang - Indah Puspita Arum; Arif Fadli Muchlis; Bafirman; Liza (Jurnal IKEOR, 2023)
The problem in this research is that the nutritional status of students is not known and the availability of playing infrastructure in schools is inadequate, as well as the habits of students consuming unhealthy food. This study aims to determine whether there is a significant relationship between nutritional status and exercise habits on the level of physical fitness of SD 2 Angkasa students, Padang City. This type of research is correlational which aims to see the relationships between variables. The subjects of this research were the students of Angkasa Elementary School 2, Padang City. The population in this study were all students and a sample of 48 students were obtained using a purposive sampling method. The instruments used were (1) variable nutritional status by measuring height and weight, using the BMI formula, (2) exercise habit variable obtained from the spread of armature with the Likert scale, and (3) physical fitness by taking the Indonesian physical fitness test (TKJI ). Data were analyzed by product moment correlation and multiple correlation. The results showed that (1) the correlation between exercise habits and physical fitness (rₓᵧ) 0.282 < r tab (0.284), (2) nutritional status and physical fitness value (rₓᵧ) 0.217 < r tab (0.284), (3) status nutrition and exercise habits together with physical fitness as evidenced by the multiple correlation coefficient (rₓᵧ) 0.255 < r tab (0.288). From the results of the study it can be concluded that there is a relationship but the level of the relationship is low between nutritional status and exercise habits on physical fitness at SD Angkasa 2 Padang City.